Enhancement to source determination for Tien and Saigon rivers banks avulsion-prone zones by near-surface geophysical investigations - Thanh, Le Ngoc; Giang, Nguyen Van (Vietnam Journal of Earth Sciences, 2012)
The paper presents complex geophysical techniques as well as Ground Penetrating Radar (GPR), Very Low Frequency electromagnetic method (VLF), resistivity methods for investigating near-surface geological structure of river banks to localize interfaces and weakness zones which are related to the source of Tien and Saigon rivers banks avulsion-prone zones. The field techniques and results of complex geophysical investigations on Tan Chau-Tien river banks, Vinh Long embankment and Saigon river banks in Thanh Da were presented for assessment of landslide by present river banks structure for short time forecasting. The near-surface geological cross-sections which were established by geophysical data are proved effectiveness by some engineering wells in site. The result of investigations is scientific based for Tien and Saigon river banks landslide forecast and maintenance/regulation to preventing hazards. The near-surface geophysical methods are good tools for delineating fracture zones, saturated, weakness zones in subsurface structures of river banks to landslide forecast in near future.